Avoiding acute kidney injury in primary care: attitudes and behaviours of general practitioners and community pharmacists in Hawke's Bay - Trudi Aspden; Colin Hutchison; Dianne Vicary (CSIRO Publishing, 2020)
ABSTRACT INTRODUCTIONAwareness of the effect of acute kidney injury on patient outcomes and health systems is growing internationally. New Zealand's approach focuses on stopping consumption of 'at-risk' medicines when acute kidney injury has been established and raising awareness of the risks associated with the Triple Whammy drug combination. AIMTo explore current practices and views of Hawke's Bay general practitioners (GPs) and community pharmacists regarding patient education about medicines with potential for contributing to community-acquired acute kidney injury, with a focus on community pharmacists providing patient education regarding when to temporarily withhold 'at-risk' medicines during acute dehydrating illnesses. METHODSTwo tailored cross-sectional online anonymous surveys of GPs and community pharmacists working in Hawke's Bay were administered between 2015 and 2016. Descriptive statistics were generated from the closed-question responses and manifest content analysis was applied to the free-text responses. RESULTSTwenty-two percent (37/167) of GPs and 34% (32/95) of pharmacists responded. Most respondents, GPs (34/37) and pharmacists (25/32), self-reported expertise to educate patients on temporarily withholding 'at-risk' medicines during acute dehydrating illnesses. Twenty-nine (78%) GPs had confidence in pharmacists providing this patient education and 20 (54%) welcomed pharmacist contact regarding a Triple Whammy prescription. However, for a variety of reasons, pharmacists did not routinely provide this education or contact GPs. DISCUSSIONBoth GPs and community pharmacists reported they had expertise to provide useful patient education about 'at-risk' medicine use during acute dehydrating illnesses. Dialogue to clarify the role of the two groups would be beneficial to achieve a more coordinated approach to patient care. Relevant strategies and frameworks already exist, but national interprofessional leadership and local application would be beneficial.